Pengaruh Model Pembelajaran dan Kecerdasan Emosional Terhadap Hasil Belajar Sejarah di SMAI Al-Azhar 4 Kemang Pratama Kota Bekasi - Diyah Nur Fauziyyah (Jurnal Pendidikan Sejarah, 2017)
This aim of this research is to find out the effect of instructional model and emotional intelligence to history learning outcomes in SMAI AL AZHAR 4 Kemang Pratama Bekasi City. This research is quantitative which using experiment design treatment method by level 2x2. The population in this research are all the students in elevent grade,Sampel of research are XI iis 2 and XI iis 3 people a mount 68. Instrument that used to measure the emotional perspicacity is questioner, and instrument that used to measure the learning outcomes multiple choice. The result of this research shows that (1) the student that using cooperative learning type jigsaw is higher than student that using direct learning, (2) there is effect of interaction between instructional model and emotional intelligence, (3) History learning outcomes that using cooperative learning type jigsaw with emotional intelligence is higher than student’s direct learning. (4) History learning outcomes that using cooperative learning type jigsaw with emotional intelligence is lower than student’s direct learning.